DETECTION OF ACUTE AND RECENT HIV INFECTION BY PROVIRAL DNA PCR ASSAY - SUGUNA. E,; REVATHY A.R, (International Journal of Pharma and Bio Sciences, 2015)
The objective of this study was to standardize an HIV Proviral DNA PCR from newly infected HIV-1 individuals. Thirty five consenting, HIV-1 seropositive adults were enrolled in this study. Proviral DNA was extracted by QIAmp® DNA Mini Kit (QIAGEN, Germany) method. Gene testing was performed using Hot Start Polymerase chain reaction (PCR) to avoid non specific amplification. After amplification, the expected size of amplicon (130bp) confirmed by using 2% agarose gel electrophoresis. As a result, we standardized a specific and sensitive Hot Start PCR-based technique for newly infected HIV-1 individuals. Our finding suggests that HIV Proviral DNA PCR, which is a very sensitive tool to detect very early infection of HIV.